Endosymbiont Interactions With the Germline Underlie a Case of Evolutionary Novelty in Carpenter Ants - Durmuş Z. Ö.; MİLAT N. S.; Rajakumar A.; RAFIQI A. M. (My University, 2025)
Evolutionary novelties often arise through complex interactions among genetic, developmental, and ecological processes, yet their origins remain poorly understood. Here, we investigate the germline capsule in Camponotus (Carpenter ants) as a case of an evolutionary novelty. Using an integrated framework combining transcriptomic, morphological, and comparative developmental approaches, we characterize its molecular signatures, cellular architecture, and ontogeny. We show that germline gene–expressing cells adjacent to bacteriocytes fuse to form a multinucleated germline capsule, which subsequently contributes to the presumptive gonads, as revealed by label tracing. Despite harboring endosymbiotic bacteria like bacteriocytes, germline capsules exhibit distinct gene expression profiles. Furthermore, their phenotypic variation is developmentally modulated by bacterial presence. By examining the expression profile of germ-line specific gene (oskar) across multiple Camponotus species, we test the germline function of the capsule and its evolutionary conservation. Based on these findings, we propose a model in which the germline capsule evolved through cell fusion events enabled by developmental plasticity and shaped by interactions between host germline determinants and endosymbiotic bacteria. This study illustrates how integrating molecular, developmental, and ecological perspectives can illuminate the mechanisms underlying evolutionary innovation.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Çevre Teknolojisi; Ekoloji ve Kirlenme; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Mikrobiyal Genetik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Environmental Technology; Ecology and Pollution; Life Sciences; Molecular Biology and Genetics; Microbial Genetics; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (Age); Yaşam Bilimleri (Life); Çevre / Ekoloji; Ekoloji; Gelişimsel Biyoloji; Agriculture & Environment Sciences (Age); Life Sciences (Life); Environment/Ecology; Molecular Biology & Genetics; Ecology; Developmental Biology; Ekoloji, Evrim, Davranış ve Sistematik; Ecology, Evolution, Behavior and Systematics; cell fusion; developmental plasticity; endosymbiosis; evolutionary novelty; germline